Functional Studies of a Fibrinogen Binding Protein from Staphylococcus epidermidis - Pei, Lei (American Society for Microbiology, 1999)
A gene encoding a fibrinogen binding protein from Staphylococcus epidermidis was previously cloned, and the nucleotide sequence was determined. A portion of the gene encompassing the fibrinogen binding domain has now been subcloned in an expression-fusion vector. The fusion protein can bind to fibrinogen in a capture enzyme-linked immunosorbent assay and can be purified by fibrinogen affinity chromatography. This protein can completely inhibit the adherence of S. epidermidis to immobilized fibrinogen, suggesting that the adherence of S. epidermidis to fibrinogen is mainly due to this protein. Antibodies against this fibrinogen binding protein were also found to efficiently block the adherence of S. epidermidis to immobilized fibrinogen. Despite homology with clumping factors A and B from S. aureus (cell surface-associated proteins binding to fibrinogen), binding involved the β chain of fibrinogen rather than the γ chain, as in clumping factor A.